Dissemination of the Free Nutritious Meal Program for Students: Case Study in Rote-Ndao Regency – Indonesia - Mas’amah Mas’amah; Emanuel Sowe Leuape; Fitria Titi Meilawati; Apris A Adu; Andreas J. F. Lumba (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
ntroduction: Health has been a priority in Indonesia’s development agenda over the past two decades. One initiative is the Free Nutritious Meal Program, launched in early 2025. The program targets students, pregnant women, breastfeeding mothers, toddlers, and other groups vulnerable to nutritional deficiencies. This study examines the educational activities of the Free Nutritious Meal Program for students in Rote Ndao Regency, focusing on educational steps, media use, message formats, media exposure, and the determinants of educational agendas. Method: This qualitative research employs a case study method, with data collected through in-depth interviews, observation, and documentation. Informants were chosen through purposive sampling, and data was analyzed using methods like Pattern Matching and Explanation Building. These techniques were used to interpret the information from the viewpoints of innovation diffusion and development communication. Results: The Rote Ndao government has not yet implemented educational activities for the Free Nutritious Meal Program in a planned, direct, and systematic manner. Teachers, students, and parents primarily obtain information about the program independently through media sources. Television remains the most frequently used conventional mass medium, mainly through news broadcasts. In addition, local communities also access program information via new media. Students receive program information primarily in the form of video content, textual news narratives, and oral accounts in daily conversations. Program exposure among students in Rote Ndao Regency is relatively low, at only 14.28%. The implementation of the program’s educational activities in the regency remains suboptimal, influenced by several factors, including government educational agendas, media and information accessibility, technological competence, and communication infrastructure. Conclusion: This study concludes that the educational activities of the Free Nutritious Meal Program in Rote Ndao Regency have not been implemented optimally. It confirms that the program’s execution in the regency has prioritized operational stages while neglecting the role of communication variables as a key factor in its success. The findings may serve as a reference for stakeholders to enhance the program’s effectiveness in the future, particularly regarding the urgency of an educational agenda.